NEW TECHNIQUES OF LEARNING AND REMEMBERING ENGLISH WORDS - Nazarova Dilshodakhon Ochildinovna (Western European Studies, 2025)
This article discusses new techniques of learning and remembering English words, how to improve vocabulary by using different methods and strategies. It also discusses and demonstrates the importance of new vocabulary learning methods and strategies in teaching and learning the English language, along with suggestions and solutions from leading experts
Keywords: vocabulary retention; memorization; spaced repetition